The Roles of CCR9/CCL25 in Inflammation and Inflammation-Associated Diseases - Wu, Xue; Sun, Meng; Yang, Zhi; Lu, Chenxi; Wang, Qiang; Wang, Haiying; Deng, Chao; Liu, Yonglin; Yang, Yang (Frontiers in Cell and Developmental Biology, 2021)
Chemokine is a structure-related protein with relatively small molecular weight, which can target cells to chemotaxis and promote inflammatory response. Inflammation plays an important role in aging. C-C chemokine receptor 9 (CCR9) and its ligand C-C chemokine ligand 25 (CCL25) are involved in the regulating the occurrence and development of various diseases, which has become a research hotspot. Early research analysis of CCR9-deficient mouse models also confirmed various physiological functions of this chemokine in inflammatory responses. Moreover, CCR9/CCL25 has been shown to play an important role in a variety of inflammation-related diseases, such as CVD, rheumatoid arthritis, hepatitis, inflammatory bowel disease, asthma and etc. Therefore, the purpose of this review gives an overview of the recent advances in understanding the roles of CCR9/CCL25 in inflammation and inflammation-associated diseases, which will contribute to the design of future experimental studies on the potential of CCR9/CCL25 and advance the research of CCR9/CCL25 as pharmacological inflammatory targets.